Botanical survey in thirteen montane forests of Bawean Island Nature Reserve, East Java Indonesia: Flora diversity, conservation status, and bioprospecting - TRIMANTO TRIMANTO; LIA HAPSARI (Society for Indonesian Biodiversity, 2016)
Trimanto, Hapsari L. 2016. Botanical survey in thirteen montane forests of Bawean Island Nature Reserve, East JavaIndonesia: Conservation status, bioprospecting and potential tourism. Biodiversitas 17: 832-846. Bawean Island which located between Borneo and Java islands possessed unique and distinctive abiotic and biotic resources. Botanical survey has been conducted in Bawean Island Nature Reserve. This paper reported the results of inventory study of plant bioresources in 13 montane forests of Bawean Island, discussed their conservation status, bioprospecting on some wild plant species and potential development subjected to some conservation areas. Inventory results in montane forests showed that it was registered about 432 plant species under 286 genera and 103families; comprised of 14 growth habits in which tree plants were the most dominant with about 237 species. Conservation status evaluation showed that there are at least 33 species of plants included in IUCN list comprised of 30 species categorized as least concern and 3 species considered at higher risk of extinction i.e. Podocarpus rumphii (Near Threatened); Pterocarpus indicus and Memecylon myrtilloides (Vulnerable). Bioprospecting results showed that 10 tuberous plants prospected as food sources; 19 woody plants prospected as timber sources, and 28 plants prospected as ornamental plants. There are at least 7 invasive alien plant species identifiedincluding Ageratum conyzoides, Chromolaena odorata, Eupatorium inulifolium, Lantana camara, Imperata cylindrica, Stachytarpheta jamaicensis and Themeda arguens. If well managed, the development of Bawean Island as nature-based and eco-tourism may contribute both to biodiversity conservation and alleviating prosperity of the local residents.